33 NOX1 IS REQUIRED FOR SMOOTH MUSCLE CELL ACTIVATION OF MATRIX METALLOPROTEINASE 9 AND CELL MIGRATION IN RESPONSE TO THROMBIN. (1st March 2007) - Dammanahalli, J. K.; Bhalla, R. C.; Banfi, B.; Miller, F.
Abstract : Smooth muscle cell (SMC) degradation of the extracellular matrix and migration to the intima are fundamental processes in the vascular response to injury. NADPH oxidase-derived reactive oxygen species (ROS) are involved in development of vascular disease; however, the specific contribution of Nox1 and Nox4, the primary catalytic subunits of NADPH oxidase in SMC, is poorly understood. We hypothesized that Nox1-derived ROS mediate thrombin-dependent activation of matrix metalloproteinase 9 (MMP-9) and migration of SMCs. Studies were performed in SMCs cultured from the aorta of Nox1 null and littermate control mice. Thrombin (2 U/mL) increased superoxide levels in control SMCs, as measured by dihydroethidium, and this response was inhibited by the flavoenzyme inhibitor diphenylene iodonium (DPI, 10 μM). In contrast, thrombin failed to increase ROS in Nox1 null SMCs. Previous studies have identified Src and mitogen-activated protein kinases as key redox-dependent regulatory proteins in thrombin-stimulated responses. Five minutes following thrombin stimulation, both Src and ERK1/2 phosphorylation were significantly decreased in Nox1 null SMCs compared with normal SMCs, measured by densitometry of Western blots. In addition, in response to thrombin, epidermal growth factor receptor (EGFR) phosphorylation was reduced in Nox1 null VSMCs. Conditioned media was collected 24 hours after cells were treated with thrombin and MMP-9 activity measured by gelatin zymography. Thrombin increased MMP-9 more than twofold in control cells; however, thrombin failed to increase MMP-9 activity in Nox1 null cells. Using a wound-scratch assay, the number and distance of cells migrating into the injured area were markedly reduced in SMCs deficient in Nox1. In conclusion, the Nox1 subunit of NADPH oxidase is required by SMCs for thrombin-dependent activation of MMP-9 and cell migration. In addition, Nox1 generation of ROS participates in phosphorylation of Src and of ERK1/2. These findings suggest that Nox1 may play an important role in the pathogenesis of vascular disease.